Keeping out Trojan Horses: Auctions and Bankruptcy in the Laboratory - Sander Onderstal; Ailko van der Veen (Tinbergen Institute, 2011)
If a government auctions the right to market a good, continuity is likely to be of significant importance. In a laboratory experiment, we compare the effects of bidders' limited liability in the first-price sealed-bid auction and the English auction in a common value setting. Our data strongly reject our theoretical prediction that the English auction leads to less aggressive bids and fewer bankruptcies than the first-price sealed-bid auction. X-cursedness gives a robust explanation of our experimental observations, in contrast to risk aversion and asymmetric equilibria.
Keywords: C91; D44; L41; 330; Auctions; Bankruptcy; Laboratory Experiment; Insolvenz; Auktionstheorie; Test